URGENSI DAN IMPLEMENTASI TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) DALAM PEMBELAJARAN MATEMATIKA - Nurwahid, Mohammad (Mathematics Education And Application Journal (META), 2024)
In the field of mathematics, the main challenge teachers face is how to make complex and abstract material easier for students to understand. Technology, if used appropriately, can help close this gap. Technological Pedagogical and Content Knowledge (TPACK) is a framework to help teachers integrate technology into their teaching in an effective way. The aim of writing this article is to provide information about the urgency and application of TPACK in mathematics learning. This research uses a literature review, data obtained from international and national journals in the last ten years, data analysis uses an analysis model by Miles which includes three stages, namely the process of data collection, verification and drawing conclusions through document research. The results of this research are the urgency of TPACK in mathematics learning, including increasing student involvement, increasing conceptual understanding, personalized learning, developing 21st century skills. Meanwhile, the application of TPACK in mathematics learning can be done by identifying mathematical concepts or content, identifying technology that is appropriate to the content, planning learning by integrating technology, conducting assessments, providing constructive feedback, carrying out reflection and continuous improvement.